Antithrombotic therapy in the elderly and senile age: the consensus opinion of experts of the Russian Association of Gerontologists and Geriatricians and the National Society of Preventive Cardiology - O. N. Tkacheva; N. M. Vorobyeva; Yu. V. Kotovskaya; N. K. Runikhina; I. D. Strazhesco; S. V. Villevalde; O. M. Drapkina; A. L. Komarov; Ya. A. Orlova; E. P. Panchenko; N. V. Pogosova; E. V. Frolova; et al. (Кардиоваскулярная терапия и профилактика, 2021)
В данном документе обсуждаются особенности АТТ у лиц пожилого и старческого возраста в различных клинических ситуациях.